Prefeeding Oromotor Stimulation Program for Improving Oromotor Function in Preterm Infants — A Randomized Controlled Trial - Arora, Karan; Goel, Sorabh; Konde, Nimisha; Panchal, Harshad; Hegde, Deeparaj (Indian pediatrics, 2018)
To determine effect of Premature Infant Oral Motor Intervention program on oro-motor function and time to full independent wati spoon feeds in preterm infants. 30 preterm infants between 28–32 weeks of gestation on full gavage feeds of 150 mL/kg/day were randomized to receive either pre-feed oro-motor stimulation using Premature Infant Oral Motor Intervention (structured stimulation) or sham intervention (unstructured stimulation). Improvement in mean (SD) Neonatal Oro-Motor Assessment Scale (NOMAS) over 7 days from baseline was significantly higher in the study group infants as compared to control group (9.25 (1.73) vs 4.79 (1.52), P=0.001). Infants in the study group reached full independent wati spoon feeds significantly earlier than the infants in control group (4.0 (0.8) d; vs 6.64 (1.0) d; P=0.001). There was significant increase in weight gain after enrolment in infants in study group compared to those in control group. Oral stimulation program improves the oro-motor skills and growth velocity in 28–32 week preterm infants. There is decreased transition time from gavage to full independent feeds by mouth.
Keywords: Breestfeeding; Stimulation; Prematurity; Neonate